Study guides

☆☆

Q: What is an equivalent expression to (3r) plus (ar) plus (4r)?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

It is in its simplest form: 4r+r = 5r

4r+4g

4r

2r + 2s = 50 2r - s = 17 therefore 4r - 2s = 34 Add so that you can eliminate one of the variables: 2r + 2s = 50 4r - 2s = 34 ---------------- 6r + 0s = 84 Solve for r: 6r = 84 r = 14 Substitute r into one of the original equations: 2(14) + 2s = 50 28 + 2s = 50 2s = 22 s = 11 Doublecheck with the other original equation: 2(14) - 11 = 28 - 11 = 17

Area of the original circle = πr2 Area of enlarged circle = π(4r)2 = π16r2 The enlarged circle is 16 time as big as the original circle.

Related questions

It simplifies to: 2s+4R

7r = 3r - 527r (- 3r) = 3r - 52 (- 3r)4r = - 524r / 4 = -52 / 4r = -13

-13

(3r + 18)/12 = (4r - 48)/4Multiply both sides by 12: (3r + 18) = 3*(4r - 48)or: 3r + 18 = 12r - 144Subtract 3r from both sides: 18 = 9r - 144Add 144 to both sides: 162 = 9rDivide both sides by 9: 18 = rAnswer: r = 18

4r + 4 = 5r 4r - r = 3r 4r x r = 4r^2 4r/r = 4

4r + 8rs + 28r 4r is a factor of every every term so the expression can be written 4r(1 + 2s +7) NOTE : The original expression can be simplified to 8rs + 32r and thus the factored expression becomes 4r(2s + 8).

4r +3 = 3r-2 r + 3=-2 r=-5 basically collect terms so that you get one coefficient of r (in this case 4r on one side and 3r on the other. To get the three r over to the other side you subtract 3r on both sides.) Then r+ 3=-2, so that's simple algebraic manipulation.

6

It is 4r + 12s

-2=4r+s s=-4r-2 or s=-(4r+2)

Since 4R and R both contain a like term (R), you can combine them: 5R would be 4R plus R simplified

s = -2 -4r

People also asked